An evaluation of wrong-way crashes from highway ramps in Kansas, USA. Issue 3 (3rd July 2019) - Fitzsimmons, Eric J.; Cunningham IV, Jack R.; Dissanayake, Sunanda; Liang, Jia
Abstract: Wrong-way crashes on limited access highways continue to be a serious problem for state highway agencies and communities. These crashes are more likely to result in fatalities or serious injuries than other traffic incidents, due to vehicles travelling at high speeds, often involved on a roadway with limited vertical space and time to avoid a crash. This research study focused on wrong-way crashes that occurred on highways in the State of Kansas. Although these crashes represent a very small portion of crashes, wrong-way crashes were found to have a higher rate of fatalities and injuries as compared to other crash types. Using ten years of crash data, it was found that a typical wrong-way crash occurred under no adverse weather conditions, at a non-intersection location, in daylight or with streetlights present, involved alcohol or drugs, and resulted in a fatality or serious injury. An ordinary logistic model was developed to identify significant characteristics of wrong-way crashes. The model indicated that drivers under the influence of alcohol or drugs was found to be a significant in both fatal and injury wrong-way crashes. It was also found that certain lighting conditions were also significant, along with use of safety equipment and drivers over the age of 55 years old. Additional research is needed to further investigate wrong-way crashes and their causalities in Kansas on other roadway facilities including rural at-grade divided intersections.